Distinct bone marrow immunophenotypic features define the splicing factor 3B subunit 1 (SF3B1)‐mutant myelodysplastic syndromes subtype. (25th March 2021) - Duetz, Carolien; Westers, Theresia M.; in 't Hout, Florentien E. M.; Cremers, Eline M. P.; Alhan, Canan; Venniker‐Punt, Bianca; Visser‐Wisselaar, Heleen A.; Chitu, Dana A.; de Graaf, Aniek O.; Smit, Linda; Jansen, Joop H.; van de Loosdrecht, Arjan A.
Summary: Splicing factor 3B subunit 1 ( SF3B1 ) mutations define a distinct myelodysplastic syndromes (MDS) patient group with a relatively favourable disease course and high response rates to luspatercept. Few data are available on bone marrow phenotype beyond ring sideroblasts in this subgroup of patients with MDS. In the present study, we identified immunophenotypic erythroid, myelomonocyte and progenitor features associated with SF3B1 mutations. In addition, we illustrate that SF3B1 ‐mutation type is associated with distinct immunophenotypic features, and show the impact of co‐occurrence of a SF3B1 mutation and a deletion of chromosome 5q on bone marrow immunophenotype. These genotype–phenotype associations and phenotypic subtypes within SF3B1 ‐MDS provide leads that may further refine prognostication and therapeutic strategies for this particular MDS subgroup.